Implementasi Etika Bisnis dalam Menjalankan Bisnis pada UMKM di Desa Punti - Sulistianingsih Sulistianingsih; Anfani Anfani; Nurfitrah Nurfitrah; Aida Zulwahidah; Kartin Aprianti (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
The application of business ethics to Micro, Small and Medium Enterprises (MSMEs) in Punti Village is very important to increase competitiveness and business desirability. This research aims to examine the application of business ethics in running a business among MSMEs in Punti Village, as well as its impact on business development and relationships with consumers. The method used is qualitative research with a case study approach on several MSMEs in Punti Village. The research results show that implementing business ethics which includes honesty, transparency, and social responsibility can increase consumer trust, strengthen relationships with suppliers, and create positive social change in the village. However, challenges in implementing business ethics include limited knowledge and local customs which sometimes conflict with the principles of business ethics.